Lipid Metabolism and energetic expenditure during exercise - Fernando Roberto De-Oliveira; Flávio De Oliveira Pires; Adriano Eduardo Lima-Silva; Maria Augusta Peduti Dal Molin Kiss (Universidade Federal de Santa Catarina, 2008)
The goal of this study was to present a new perspective on the relationship between lipid metabolism and the intensity/duration of exercise and energy expenditure. The idea was to use the second lactate threshold as a marker of the best ratio between energy expenditure and duration of exercise. From the literature review and analyses of experimental data, it was demonstrated that the second lactate threshold mark is the point at which the best ratio occurs between substrate oxidation rate and duration of effort. This means that any low intensity exercise performed below the second lactate threshold will require more time to achieve the same energy expenditure as exercise performed at the second lactate threshold. On the other hand, exercise performed above the second lactate threshold has a higher substrate oxidation rate, but, due to the shorter time for which the effort can be sustained, the total energy expenditure is less. These considerations have important practical applications in training schedules for reducing body fat. ResumoO foco desse trabalho é apresentar um ponto de vista diferenciado, referente ao inter relacionamento de metabolismo lipídico, intensidade/duração de exercício e gasto energético. A idéia central foi utilizar o segundo limiar de lactato como indicador da melhor relação entre gasto energético e tempo de exercício. A partir de dados levantados na literatura e das análises realizadas com estudos experimentais, foi demonstrado que o segundo limiar de lactato corresponde ao ponto de melhor relação entre a taxa de gasto energético e o tempo de esforço. Isso signifi ca que qualquer exercício de baixa intensidade, realizado abaixo do segundo limiar de lactato, precisaria de mais tempo para obter o mesmo gasto energético do que o realizado na intensidade do segundo limiar. Por outro lado, exercícios acima do segundo limiar de lactato apresentam maior taxa de gasto energético, mas devido ao menor tempo de sustentação do esforço, o gasto energético total é menor. Estas considerações têm importantes aplicações práticas no que se refere aos programas de treinamento para redução da massa de gordura corporal.